PENDEKATAN KOMPREHENSIF DALAM PENANAMAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR TAMAN MUDA JETIS YOGYAKARTA - Chairiyah, Chairiyah; Nadziroh, Nadziroh (Prodi PGSD FKIP Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to comprehend the implementation of character education with a comprehensive approach at Taman MudaJetis Elementary School Yogyakarta, to find out the obstacles in the implementation of character education with a comprehensive approach at Taman MudaJetis Elementary School Yogyakarta, and to know the solution to solve the obstacles in the implementation of character education with comprehensive approach at SD Taman MudaJetis Yogyakarta. This study uses a qualitative method. The data collecting technique uses in-depth interviewand direct observation. The steps of data analysis utilize Miles and Huberman model, which are data presentation, data reduction, and confirmation, while validity test data includes internal validity test, external validity, reliability, and objectivity.The results of this study indicate that character education applied in schools is not taught in the form of special subjects but integrated into all lessons with a comprehensive approach that includes inclusion, modelling, value facilitation, and soft skill development. The obstacles in the implementation of character education are the misused of the advancement of science and technology by learners, family and society factors and environment that does not support the learning, low teacher competence especially new teachers in implementing character values. The strategy to break the barriers in implementing character education is to form qualified and professional teachers by including teachers in professional training at local and national levels and increasing synergies between schools, families and communities.